Navigating Diverse Career Paths: Students’ Perception on Career Counseling Need in Islamic Universities - Awad, Faizah Binti; Shaleh, Muh.; Rezki, Anita; Jufra, Arlita Aristianingsih; Tonn-Meller, Horst (Jurnal Kajian Bimbingan dan Konseling, 2024)
This research aims to explore the needs of career counseling services for students in different majors in Islamic universities, and identify how these services can be tailored to meet their unique needs. A mixed-methods approach was used to collect and analyze data from undergraduate students in diverse majors at an Islamic university in Kendari. The study found that students in certain majors require more specific counseling, such as information on job market trends and technical skills development. Additionally, the study suggests that career counseling services can be tailored to meet the specific needs of students in diverse majors by providing specialized workshops and networking events, as well as spiritual counseling and guidance. Providing a combination of in-person and online resources can also be highly beneficial for students' career development. The findings of this study can inform the development of more effective and tailored career counseling services for students in Islamic universities, and help ensure that graduates are well-prepared for the job market and can make meaningful contributions to society.